PERBANDINGAN PENGGUNAAN TEKNIK HEDGING DENGAN OPEN POSITION DALAM MEMINIMALISASI NILAI HUTANG IMPOR - Nurmalasari, Made Ratih; Purnawati, Ni Ketut (E-Jurnal Manajemen, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 The currency exchange rate fluctuations result in the value of company import debt payment becomes uncertain since it could change at any moment. The company can run the hedging technique to protect its value of import debt. This study aims to determine the difference of the value of import debt while using the forward contract hedging, money market hedging, and currency option hedging without using the hedging (open position) technique. This study used 15 import transactions of PT. Sayap Garuda Indah during early in 2012 until early in 2013. The analysis technique used is T -test. The results of this study show that there is no difference of the company’s value of the import debt, while using the forward contract hedging, money market hedging, and currency option hedging, with open position. However, among those three hedging techniques, the minimum value of import debt is when the company runs the forward contract hedging. Keywords: Forward Contract Hedging , Money Market Hedging, Currency Option Hedging, Open Position, Import Debt Value /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}